Relationship between anthropometric, physiological and physical characteristics with success of female taekwondo athletes - Zahra Hosseınzadeh; Mani Izadı; Hamid Arazı (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to investigate the relationship between anthropometric, physiological and physical characteristics with success of elite female taekwondo athletes. Forty subjects were selected from elite female taekwondo athletes who won medals in regional and national championships. Individual information forms were completed. The mean age, height and body mass index of subjects were 17.84±3.67 years, 167.56±6.92 cm and 19.12±2.45 kg/m2 respectively. All subjects were assessed for height, weight, lengths, girths, body mass index, waist-to-hip ratio and skin-fold thickness. Percentage of body fat was calculated from the sum of 3 site measurements of skin-fold thickness. Aerobic and anaerobic power were also calculated using by cooper and Sargent vertical jump tests respectively and then by placing into the standard recommended equations. Speed, agility, muscular endurance and flexibility were assessed using by 36m sprint, 4×9m shuttle run, push-ups and sit-and-reach tests respectively. From all of anthropometric, physiological and physical characteristics, anaerobic and aerobic power, body mass index and fat percentage, speed and agility were significantly related to success and had more importance for taekwondo athletes. Thus, these characteristics have a major effect on taekwondo specially, in championship goals and should be considered in talent identification and training planning of this sport.